Comparative study between preoperative embolization and non embolization in juvenile nasopharyngeal angiofibroma resection - Tahany Rabie; Mohamed Qamar El-Sharnoby; Jermen Gamal Shokury Wasef; Omar Yassin (The Egyptian Journal of Otolaryngology)
Abstract Objective To compare the results of resection for juvenile nasopharyngeal angiofibroma (JNA) by endoscope between cases that have been embolized preoperatively by transarterial approach and cases that have not been embolized regarding recurrence rates, post-operative complication rates, mean operative time, and mean intraoperative blood loss. Data sources According to PRISMA guidelines, searches were conducted on PubMed, Cochrane, Embase, Scopus, and Google Scholar for publications from 2003 till 2023. Patients and methods In this meta-analysis seventeen original articles in English language studying the surgical removal of JNA by endoscope with and without preoperative transarterial embolization were included. Recurrence rate, rates of complications, amount of blood lost during surgery and surgical time were obtained. Results The main findings were that preoperative transarterial embolization (TAE) seemed to offer improvement of outcomes regarding the intraoperative blood loss, surgical time and recurrence rate but higher complication rate compared with non-embolization. JNA recurrence rate in embolized patients was lower than in non-embolized patients (M-H RR = 0.843 (95% CI: 0.403 – 1.765), I2 < 0.001%, p = 0.651), intraoperative blood loss was less toward embolized group than non-embolized group (SMD = -2.166 (95% CI: -3.745 – -0.586), I2 = 93.440%, p = 0.007), surgical time was less toward embolized group than non-embolized group (SMD = -1.531 (95% CI: -4.169 – 1.107), I2 = 93.125%, p = 0.255), the postoperative complication rates were less toward non-embolized group than embolized group (M-H RR = 1.042 (95% CI: 0.367 – 2.958), I2 < 0.001% p = 0.939). Conclusion Patients had preoperative transarterial embolization had better outcome regarding intraoperative mean blood loss, operative time and recurrence rate but higher postoperative complication rates.